The Impact of Physical Activity on Cognitive Function Among Early Elderlies - Domingo , Jupiter Y.; Alviar Jr, Ronald T.; Gonayon, Michaela G.; Damo, John Leones (Health Access Journal, 2026)
Aging is associated with gradual changes in memory, attention, and executive functioning that may compromise independence and quality of life among older adults. Regular physical activity has been proposed as a modifiable strategy to preserve cognitive health, although evidence remains inconsistent in community-based settings. This study aimed to determine the relationship between physical activity and cognitive function among early elderlies in Barangay Leonarda, Tuguegarao City, Philippines. A quantitative correlational design was used involving 125 adults aged 65–74 years selected through purposive sampling. Physical activity was measured using the International Physical Activity Questionnaire, and cognitive function was assessed using the revised Everyday Memory Questionnaire. Data were analyzed using descriptive statistics, Spearman’s rank correlation, and one-way analysis of variance at a 0.05 significance level. Respondents demonstrated high physical activity (mean = 5,461.30 MET-min/week), with 77% classified as highly active. Overall cognitive function was relatively stable (mean = 3.00), indicating only occasional cognitive lapses. Spearman’s rank correlation analysis revealed a weak negative relationship between physical activity and cognitive function indicating that higher physical activity levels were not significantly associated with better cognitive performance. Weak negative correlations were likewise observed across all cognitive domains, but none reached statistical significance. No significant differences in cognitive function were found across physical activity levels (ANOVA, these findings suggest that physical activity was not significantly associated with cognitive function among early elderlies in this community and that other biological, psychosocial, and environmental factors may play a more substantial role in influencing cognitive health.